2021
DOI: 10.1021/acsami.1c13770
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Protein–Polymer Bioconjugation via Photoinduced RAFT Polymerization Using High Loading Heterogeneous Catalyst

Abstract: Light-driven polymerization, such as photoinduced electron/energy transfer−reversible addition−fragmentation chain transfer (PET-RAFT) polymerization, enables biological benign conditions and versatile functional polymer structure design, which is readily used in protein−polymer bioconjugates. However, conventional metalloporphyrinic homogeneous catalysts for PET-RAFT polymerization suffer from limited aqueous solubility and tedious purification. Here we demonstrate the design of PET-RAFT photocatalyst from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…The deconvolution of high-resolution C 1s core-level spectra comprised three peaks with respective binding energies (BEs) at 284.6 eV for -C-C/-CH species, 285.9 eV for -C-N species and 288.1 eV for O-C═O species (Figure 2b,d and Figure S5b, Supporting Information). [17] Besides, the [-C-N]/[O-C═O] peak component area ratio approximated 2:1 after deconvolution were consistent with the molecular structure of ZnTCPP units except for a marked difference in specific element intensity for these MOF samples. The deconvolution of high-resolution C 1s core-level spectra comprised two peaks with BEs at 398.2 eV for the pyrrole nitrogen ((C)═N-) and 399.7 eV for amine nitrogen ((C)-N-) doped in the carbon matrix (Figure 2b′,d′ and Figure S5b′, Supporting Information).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The deconvolution of high-resolution C 1s core-level spectra comprised three peaks with respective binding energies (BEs) at 284.6 eV for -C-C/-CH species, 285.9 eV for -C-N species and 288.1 eV for O-C═O species (Figure 2b,d and Figure S5b, Supporting Information). [17] Besides, the [-C-N]/[O-C═O] peak component area ratio approximated 2:1 after deconvolution were consistent with the molecular structure of ZnTCPP units except for a marked difference in specific element intensity for these MOF samples. The deconvolution of high-resolution C 1s core-level spectra comprised two peaks with BEs at 398.2 eV for the pyrrole nitrogen ((C)═N-) and 399.7 eV for amine nitrogen ((C)-N-) doped in the carbon matrix (Figure 2b′,d′ and Figure S5b′, Supporting Information).…”
Section: Resultssupporting
confidence: 71%
“…The high degree of oxygen tolerance and catalyst reusability could be harnessed to enable PET‐RAFT polymerization to occur without prior deoxygenation suggesting the efficiency with which Zn‐ZnPPF‐2D can remove both dissolved oxygen and atmospheric oxygen diffusing into solution. [ 17,49,50 ] The unimodal molecular weight distribution confirmed that the Zn‐ZnPPF‐2D mediated PET‐RAFT polymerization in aerobic condition did not affect the polymerization kinetics and living characteristics, expect for a prolonged induction period resulting from continuous oxygen photosensitization and consumption (Figure S11, Supporting Information). Noting the broadband absorption characteristics of Zn‐ZnPPF‐2D nanosheets, PET‐RAFT polymerization was next extended to a range of hydrophilic acrylamides (including N,N ‐dimethylacrylamide (DMA), N,N ‐diethylacrylamide (DEA), N ‐isopropylacrylamide (NIPAM), and N ‐hydroxyethyl acrylamide (HEAA)) and hydrophobic acrylates (including methyl acrylate (MA), butyl acrylate (BA), isobornyl acrylate (IBA) and tetrahydrofurfuryl acrylate (THFA)) in a 96‐well deep well plate to determine any impediments to the polymerization.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Because they can easily be separated and reused, heterogeneous catalysts play an important role in various polymerizations, and increasing attention has been paid to this field in recent years. [30][31][32][33][34][35][36][37][38][39][40][41] However, the use of heterogeneous catalysis in LCP is very limited. Few studies of heterogeneous catalysis of LCP have been reported to date.…”
Section: Introductionmentioning
confidence: 99%